Maternal Knowing and Social Networks: Understanding First-Time Mothers' Search for Information and Support Through Online and Offline Social Networks. (August 2018) - Price, Sheri Lynn; Aston, Megan; Monaghan, Joelle; Sim, Meaghan; Tomblin Murphy, Gail; Etowa, Josephine; Pickles, Michelle; Hunter, Andrea; Little, Victoria
The postpartum period is an exciting yet stressful time for first-time mothers, and although the experience may vary, all mothers need support during this crucial period. In Canada, there has been a shift for universal postpartum services to be offered predominantly online. However, due to a paucity of literature, it is difficult to determine the degree to which mothers' needs are being effectively addressed. The aim of this study was to examine and understand how first-time mothers accessed support and information (online and offline) during the first 6 months of their postpartum period. Using feminist poststructuralism methodology, data were collected from focus groups and e-interviews, and analyzed using discourse analysis. Findings indicate that peer support is greatly valued, and mothers often use social media to make in-person social connections. Findings highlight how accessing support and information is socially and institutionally constructed and provide direction for health professionals to provide accessible postpartum care.